Formulation and Particle Size Reduction Improve Bioavailability of Poorly Water-Soluble Compounds with Antimalarial Activity. (12th May 2013) - Wang, Hongxing; Li, Qigui; Reyes, Sean; Zhang, Jing; Xie, Lisa; Melendez, Victor; Hickman, Mark; Kozar, Michael P.
Abstract : Decoquinate (DQ) is highly effective at killing malaria parasites in vitro ; however, it is extremely insoluble in water. In this study, solid dispersion method was used for DQ formulation which created a suitable physical form of DQ in aqueous phase for particle manipulation. Among many polymers and surfactants tested, polyvinylpyrrolidone 10, a polymer, and L- α -phosphatidylcholine or polysorbate, two surfactants, were chosen as DQ formulation components. The formulation particles were reduced to a mean size between 200 to 400 nm, which was stable in aqueous medium for at least three weeks. Pharmacokinetic (PK) studies showed that compared to DQ microparticle suspension, a nanoparticle formulation orally dosed to mice showed a 14.47-fold increase in area under the curve (AUC) of DQ plasma concentration and a 4.53-fold increase in AUC of DQ liver distribution. WR 299666, a poorly water-soluble compound with antimalarial activity, was also tested and successfully made into nanoparticle formulation without undergoing solid dispersion procedure. We concluded that nanoparticles generated by using appropriate formulation components and sufficient particle size reduction significantly increased the bioavailability of DQ and could potentially turn this antimalarial agent to a therapeutic drug.